Transition-Metal-Free Hunsdiecker Reaction of Electron-Rich Arenecarboxylic Acids and Aryl Aldehydes in Water - Li, Zejiang; Wang, Kunkai; Liu, Zhong-Quan (Synlett, 2014)
An I2O5-mediated decarboxylative and decarbonylative bromination/iodination of electron-rich arenecarboxylic acids and aryl aldehydes by using KBr/KI as the halogen source in water has been developed. This scalable, low-cost, and transition-metal-free halogenation allows convenient access to aryl bromide and iodide under mild conditions.
Keywords: I2O5-mediated; decarboxylative; decarbonylative; bromination; iodination; arenecarboxylic acids; aryl aldehydes